Moving from nos/otros to nosotros: a transcendent approach to sustainable development. Issue 2 (17th February 2016) - Upton, Sarah De Los Santos
ABSTRACT: Traditional top-down approaches to community development reinforce nos/otros binaries within provider/recipient relationships; transcendent approaches, on the other hand, create space for nosotros collaborative development. This article describes an instance of the nos/otros binary, in which a foreign volunteer in a rural community in Ecuador assumed the role of practitioner and limited community members' roles to recipients or beneficiaries of her development projects. Inspired by findings from this experience, the article presents a case study highlighting an alternative, transcendent, nosotros approach in Albuquerque, New Mexico, where community members work together to imagine, implement, and sustain projects.